Digital Audio Workstation - Leider Colby (McGraw Hill, 2004)
With this book and a little imagination, any musician or hobbyist can create professional music on their desktop. Written by a renowned digital music expert, this book teaches the complete digital audio workstation process, from outfitting a computer with necessary hardware and software, recording with the proper microphones, using DAW power to create perfectly modulated mixes, to finally mastering down into a completely professional finished product.